2022
DOI: 10.1155/2022/8981618
|View full text |Cite|
|
Sign up to set email alerts
|

The Development Relationship between Cross-Border e-Commerce and Internet of Things Technology Coupling in Digital Economy Based on Neural Network Model

Abstract: Compared with the traditional trading model, the problem of information asymmetry in export cross-border e-commerce (CBEC) transactions actually exists. Since the buyers and sellers of export CBEC are located in different countries, it is difficult for both parties to make accurate judgments on each other’s credit. Besides, the number of export CBEC financing is relatively small, and the financing situation is not optimistic. Fortunately, the Internet of Things (IOT) technology has a wide range of applications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The digital trade, as a transaction based on Internet technology, is defined by US International Trade Commission [19]. The Internet emergence facilitates 24/7 global online electronic commerce.…”
Section: Cross-border E-commercementioning
confidence: 99%
“…The digital trade, as a transaction based on Internet technology, is defined by US International Trade Commission [19]. The Internet emergence facilitates 24/7 global online electronic commerce.…”
Section: Cross-border E-commercementioning
confidence: 99%
“…However, the digital economy still shows a thriving trend in such an environment. Related products such as online teaching [21][22][23], telemedicine [24], and electronic commerce [25][26][27][28][29] have played an essential role. Developing the digital economy is a critical path to achieving economic recovery for countries in the post-epidemic era.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%